Volar dislocation of four carpometacarpal joint: A rarest injury (International Journal of Biomedical Research, 2014)
This article reports a case of young male grieved with fracture dislocation of the four carpometacarpal (CMC) joints dislocation due to motor vehicle collision. Volar- radial deviation of the second and third CMC joints and volar- ulnar deviation of fourth and fifth CMC joints were observed. Patient was treated with closed reduction and fixed with 0.045 K wires. First wire was placed in third metacarpal and capitate and second wire was placed from fifth metacarpal base to the proximal row of carpals. Despite all effort complete reduction at fourth and fifth CMC joint was not achieved. Follow up radiographs at one month showed satisfactory reduction and patient is performing well till the last follow up. Intensive postoperative physiotherapy is vital to achieving a satisfactory outcome.